Helping doctors become better doctors: Mary Lobjoit—an unsung heroine of medical ethics in the UK - Brazier, Margaret R (BMJ Group, 2012)
Medical Ethics has many unsung heros and heroines. Here we celebrate one of these and on telling part of her story hope to place modern medical ethics and bioethics in the UK more centrally within its historical and human contex.